Kh. Muhajirin Amsar Contribution on Legal Hadith Interpretation - Masykur Hakim (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2015)
The word 'contribution' is originally derived from English word which means to help or a donations, for example